2008
DOI: 10.1086/525259
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of Gastroenteritis during 2006 Were Associated with the Spread of Norovirus GII.4 Variants 2006a and 2006b

Abstract: The global increase in norovirus-associated gastroenteritis in 2006 was linked to the emergence of 2 novel GII.4 variants, 2006a and 2006b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
158
2
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 37 publications
15
158
2
1
Order By: Relevance
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, the incidence of general practitioner consultations for norovirus was only slightly lower than that from a recent study in Germany, which used RT-PCR diagnosis for norovirus, but again this study had a narrower case definition for IID (2 or more loose stools, or 2 or more vomiting episodes in 24 hours) (21). The incidence of norovirus-associated IID may also have been higher than normal during our study because a new variant of norovirus emerged during 1995 and 1996 (22)(23)(24); emergence of norovirus variants has been associated with increased disease incidence (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 84%
“…GII-4 was also the prevalent genotype that circulated in Belém in another study of samples collected in the years of 1992-1994 and 1998-2000 (data not shown). Many articles report a marked increase on the circulation of GII-4 strains since the 1990s, with growing genetic variability, that were related either with extensive 5,31,43 outbreaks and sporadic cases .…”
Section: Frommentioning
confidence: 99%
“…The genogroup II detected in the untreated wastewater at higher rate, as confirmed in caused a multitude of epidemics of gastroenteritis worldwide [34] . For several years the strains of genotype II, especially strain GII4, have shown worldwide and a vast geographical distribution due to contamination from person to person during epidemics [35][36][37] .…”
Section: Discussionmentioning
confidence: 84%